Analysis On the Characteristic Aroma Components of Chrysanthemum indicum var. aromaticum - Jian, L.; Sun, M.; Zhang*, Q.X. (Asian Journal of Chemistry, 2014)
Volatiles from all over Chrysanthemum indicum var. aromaticum had been analyzed by gas chromatography-mass spectrometry (GC/MS) combined with direct thermal desorption (DTD). The results showed that the volatile constituents of Chrysanthemum indicum var. aromaticum were distinct from the other wild related species. More floral scent constitutes were detected in Chrysanthemum indicum var. aromaticum with higher amounts of fatty acid derivatives and benzenoids. Thujone was found to be the characteristic components of Chrysanthemum indicum var. aromaticum, which occupying the biggest percentage in the volatiles of flowers, leaves and stems.